ANALYSIS OF AVAILABILITY OF HOTS IN PHYSICS EXAM QUESTIONS AT SENIOR HIGH SCHOOL IN LIMA PULUH KOTA DISTRICT - Bella Salsa; Yenni Darvina; - Hufri; Silvi Yulia Sari (Universitas Negeri Padang, 2021)
The 2013 curriculum requires students to have thinking skills, such as Higher Order Thinking Skills (HOTS). One strategy to train students' higher-order thinking skills is to apply HOTS questions in the learning evaluation. Through evaluation, the teacher can determine the level of students' skills in higher-order thinking. Preliminary observations show that the Physics exam questions use in SHS in Lima Puluh Kota District have not identified whether it already contains HOTS in it. Therefore, the study conducts an analysis of the availability of HOTS on physics questions at SHS in Lima Puluh Kota District. This research is descriptive research with a qualitative approach. The data population in this study are all SHS in Lima Puluh Kota District. The sample in this study is six SHS in Lima Puluh Kota District. Sampling for schools carries out using the Proportionate Stratified Random Sampling technique. The research data takes using the instrument of analysis of the questions presented and collecting data through documentation. Based on the analysis, it is found that the percentage of HOTS availability on the questions for each skill is as follows. Transfer one concept to another 19.98%, process and applying information 40.50%, find connections from different kinds of information 32.23%, use the information to solve problems 36.67%, critically examine ideas and information 8 .10%. Based on these data, it can be concluded that the percentage of the availability of HOTS in physics questions for senior high schools in Lima Puluh Kota District is 27,9%, with the category of less available